First Deployment and Validation of in Situ Silicate Electrochemical Sensor in Seawater - Barus, Carole; Chen Legrand, Dancheng; Striebig, Nicolas; Jugeau, Benoit; David, Arnaud; Valladares, Maria; Munoz Parra, Praxedes; Ramos, Marcel E.; Dewitte, Boris; Garçon, Véronique (Frontiers in Marine Science, 2018)
An electrochemical sensor is proposed to measure silicate concentration, in situ, in the ocean without any addition of liquid reagent. From the analytical principle to the laboratory prototype toward the first in situ, immersible sensor, the evolution of the mechanical design is presented and discussed. The developed in situ electronics were compared to the commercial potentiostat and gave promising results to detect low silicate signals with a limit of quantification of 1 µmol L-1.The flow rate of the pump appeared to be a crucial parameter in order to transfer the silicomolybdic complex formed from the ‘complexation cell’ to the ‘detection cell’ without dilution as well as to fill and rinse the whole circuit. The study of temperature effect revealed no influence on the electrochemical signal between ~7°C and ~21°C. Finally the sensor was successfully deployed for the very first time on a mooring off Coquimbo, Chile and also integrated onto a PROVOR profiling float in the Mediterranean Sea off Villefranche-sur-Mer, France. The data collected and/or sent through satellite were in good agreement with the 2 reference samples and previously published values illustrating the great potential of this electrochemical sensor. A 7 days silicate time series from the mooring deployment off Chile is also presented.